Revitalization of Heritage Buildings through Digital Placemaking: A Case Study of the Kebon Rojo Post Office Surabaya - Prakasyawardana, Anak Agung Gde Satyananda; Soemardiono, Bambang; Cahyadini, Sarah (Journal of Architectural Design and Urbanism, 2025)
Over time, significant changes in social, economic, and cultural aspects have profoundly influenced the function and meaning of heritage buildings. These buildings often undergo functional transformations while maintaining their historical forms, presenting challenges in preserving their architectural authenticity and historical value. The concepts of digital placemaking and Soft City theory offer potential approaches to support the preservation of heritage buildings, emphasizing community engagement and the revitalization of historical values without compromising physical authenticity. This study employs literature reviews and precedent analyses to explore how digital technology and adaptive design can meet user needs while preserving the cultural and historical significance of buildings. As a case study, the Kebon Rojo Post Office in Surabaya is analyzed through interviews and data synthesis to demonstrate the application of Soft City principles, such as optimizing the balance between open and closed spaces and utilizing digital technology to create interactive experiences. The findings show that the combination of digital placemaking and Soft City principles can produce hybrid spaces that enrich emotional and sensory connections, promote flexibility, and enhance community inclusivity. This approach integrates physical and digital elements to revitalize heritage buildings, keeping them relevant in the modern urban context. The study also highlights digital interventions such as augmented reality, adaptive lighting, and interactive digital platforms as effective tools to strengthen the cultural and historical value of heritage sites. These technologies enable more dynamic and interactive user engagement, breathing new life into heritage buildings without compromising their architectural authenticity in the digital era.